2011
DOI: 10.1002/ajh.21968
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea adherence and associated outcomes among Medicaid enrollees with sickle cell disease

Abstract: While laboratory and clinical benefits of hydroxyurea for patients with sickle cell disease (SCD) are wellestablished, few data describe the extent and implications of non-adherence. We sought to assess adherence to hydroxyurea among patients with SCD and investigate associations between adherence and clinical and economic outcomes. Insurance claims of North Carolina Medicaid enrollees (6/2000-8/2008) with SCD were analyzed. Inclusion criteria included age <65 years, continuous Medicaid enrollment 12 months be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
172
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(189 citation statements)
references
References 27 publications
12
172
5
Order By: Relevance
“…One analyzed data on Medicaid enrollees with sickle cell disease in North Carolina over the period 2000-2008 and identified subjects with filled hydroxyurea prescriptions. 11 On the basis of these data, 35% of subjects met the definition of being adherent with taking the drug, and for them, adherence was associated with a reduction in total health care costs of $6529 (P , .001). Another study examined the cost and effectiveness of hydroxyurea in reducing the frequency of pain episodes and hospitalization in pediatric sickle cell disease in South Carolina.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One analyzed data on Medicaid enrollees with sickle cell disease in North Carolina over the period 2000-2008 and identified subjects with filled hydroxyurea prescriptions. 11 On the basis of these data, 35% of subjects met the definition of being adherent with taking the drug, and for them, adherence was associated with a reduction in total health care costs of $6529 (P , .001). Another study examined the cost and effectiveness of hydroxyurea in reducing the frequency of pain episodes and hospitalization in pediatric sickle cell disease in South Carolina.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Although the MarketScan database does not identify the 12 states contributing data, those data may be more generalizable at the national level than cost estimates from individual states used in previous cost studies. 11,12,20 Of note, the claims data used to estimate hospitalization costs lacked sociodemographic information except for age (which was controlled in this analysis by restriction to 1-to 3-yearold children), gender, and, to a limited extent, race/ethnicity. 14 Another limitation of those data are the use of ICD-9 billing codes to identify children with sickle cell anemia; previous analyses of these data have found that the overall frequency of sickle cell disease among children reported to be black or African American is accurate but that information on subtypes of sickle cell disease is often lacking or imprecisely reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Similarly, Candrilli et al found that 35 % of a Medicaid population with SCD were adherent to hydroxyurea, despite the clear benefit of the therapy, as observed in the study cohort. 6 Little is known about the reasons why persons with SCD have low levels of adherence to medications and other treatments known to be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Studies reviewed herein provide increasing support of efficacy, effectiveness, and safety in both children and adults, yet indicate serious underuse for indications with the strongest evidence. 8,9,58,59 Although data on toxicity associated with hydroxyurea therapy in SCD from our review are derived from case reports or series and clinical studies where toxicities were not systematically assessed, findings are consistent with the assessment in the AHRQ review. 8 To highlight an example, the consideration of malignancy associated with hydroxyurea has been identified as a potential barrier to its use.…”
Section: Discussionmentioning
confidence: 57%